DESIGN AND BUILD AUGMENTED REALITY ON FILM POSTER USING OCCLUSION BASED DETECTION METHOD - Aap Aprilana; Agus Wahyudin; Aji Permana; Sigit Setya Kusuma (Universitas Kuningan, 2019)
Abstract Movie posters are forms of visual communication that are designed to give the impression and interest to film viewers. As one of the promotional media, the information contained in the movie poster is limited to short images and writing, so that the information conveyed is not detailed. Based on research conducted on the effectiveness of film information on film posters, it shows that the information contained in film posters is less effective, only limited to images and writing. Augmented Reality technology solves the problem by adding virtual objects in the form of video trailers, and other movie information and implementing the Occlusion Based Detection Method to detect poster markers. The result of the research that is Augmented Reality technology can be applied to design ARCinema application that can help people knowing effective information in choosing a film. Keywords : Movie Poster, Augmented Reality, Occlusion Based Detection Method.